THE Role of Chewable Tablets: An Overview: Eprosartan, LC/MS-MS, Validation, Plasma - Bhatt, Santosh Kumar; M, Kedarnagalakshman; Sharma, Mukesh (Asian Journal of Pharmaceutical Research and Development, 2021)
Chewable dosage forms for example tablets, delicate, pills, gums, chewable squares is long piece of drug specialist armamentarium. They are required to be break and bit in the middle of the teeth before administration. These tablets are given to the children who have difficulty in swallowing and to the adults who dislike swallowing. These tablets are intended to disintegrate smoothly in the mouth at a moderate rate either with or without actual chewing, characteristically chewable tablets have a smooth texture upon disintegration, are pleasant tasting and leave no bitter or unpleasant taste. Geriatric and pediatric patients and travelling patients who may not have ready access to water are most need of easy swallowing dosage forms like chewable tablets. The major formulation factors are flow, lubrication, disintegration, organoleptic properties, compressibility, compatibility and stability, which are common to regular (swallowed) and chewable tablets; however, organoleptic properties of the active drug substances are primary concern here. A formulator may use one or more approaches to arrive at a combination of formula and process that result in product with good organoleptic properties.